(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. Oxidative stress in patients with chronic kidney failure, particularly in hemodialysis patients, has been suggested to have a major role in the pathogenesis of atherosclerosis. We evaluated omega-3 fatty acids supplementation effects on oxidative and antioxidant factors in hemodialysis patients. Materials and Methods. In a clinical trial, patients on hemodialysis were divided into 2 groups in order to receive either omega-3 fatty aid capsule, 1 g 3 times a day, or placebo for 2 months. The two groups were comparable in terms of sex distribution, age, medications, diabetes mellitus, hemoglobin level, serum ferritin, and serum albumin. Blood samples taken from patients before and at the end of the study period were examined for oxidative stress markers including malondialdehyde, glutathione peroxidase, superoxide dismutase, and ferric reducing antioxidant power. Results. Seventy-five hemodialysis patients were divided into the omega-3 group (n = 37) and the control group (n = 38). Before the treatment period, the two groups were comparable in the malondialdehyde, glutathione peroxidase, superoxide dismutase, and ferric reducing antioxidant power levels. In the patients who received omega-3 fatty acids, antioxidant factors including glutathione peroxidase, superoxide dismutase, and ferric reducing antioxidant power were significantly increased after two months (P = .02, P = .02, and P = .01, respectively); however, there was no significant changes in the control group in these markers. Malondialdehyde levels were significantly reduced after the study period only in the omega-3 group (P = .007). Conclusions. The present study revealed that the supplementation with omega-3 fatty acids may result in better antioxidation status in patients on maintenance hemodialysis.